Paliperidone microemulsion for nose-to-brain targeted drug delivery system: pharmacodynamic and pharmacokinetic evaluation. (2nd January 2016) - Patel, Mrunali R.; Patel, Rashmin B.; Bhatt, Kashyap K.; Patel, Bharat G.; Gaikwad, Rajiv V.
Abstract: Objective : The objective of present study was to develop and evaluate paliperidone (PALI) loaded microemulsion (PALI-ME) for intranasal delivery in the treatment of schizophrenia. Material and methods : The PALI-ME was formulated by the spontaneous microemulsification method and characterized for physicochemical parameters. Pharmacodynamic assessments (apomorphine-induced compulsive behavior and spontaneous motor activity) were performed using mice. All formulations were tagged with 99m Tc (technetium). Pharmacokinetic evaluation of PALI in the brain was investigated using Swiss albino rats. Brain scintigraphy imaging was performed in rabbits. Results and discussion : PALI-ME was found stable with average droplet size of 20.01 ± 1.28 nm. In pharmacodynamic studies, significant ( p  < 0.05) deference in parameters estimated, were found between the treated and control groups. 99m Tc-tagged PALI solution (PALI-SOL)/PALI-ME/PALI muco-adhesive ME (PALI-MME) was found to be stable and suitable for in vivo studies. Brain-to-blood ratio at all sampling points up to 8 h following intranasal administration of PALI-MME compared to intravenous PALI-ME was found to be 6–8 times higher signifying greater extent of distribution of the PALI in brain. Rabbit brain scintigraphy demonstrated higher intranasal uptake of the PALI into the brain. Conclusion : This investigation demonstrates a prompt and larger extent of transport of PALI into the brain through intranasal PALI-MME, which may prove beneficial for treatment of schizophrenia.